A 3D microblade structure for precise and parallel droplet splitting on digital microfluidic chips. Issue 5 (14th February 2017) - Dong, Cheng; Jia, Yanwei; Gao, Jie; Chen, Tianlan; Mak, Pui-In; Vai, Mang-I; Martins, Rui P.
Abstract : 3D microblade structures were fabricated on digital microfluidic chips for precise and parallel droplet splitting of biological samples for disease diagnostics. Abstract : Existing digital microfluidic (DMF) chips exploit the electrowetting on dielectric (EWOD) force to perform droplet splitting. However, the current splitting methods are not flexible and the volume of the droplets suffers from a large variation. Herein, we propose a DMF chip featuring a 3D microblade structure to enhance the droplet-splitting performance. By exploiting the EWOD force for shaping and manipulating the mother droplet, we obtain an average dividing error of <2% in the volume of the daughter droplets for a number of fluids such as deionized water, DNA solutions and DNA–protein mixtures. Customized droplet splitting ratios of up to 20 : 80 are achieved by positioning the blade at the appropriate position. Additionally, by fabricating multiple 3D microblades on one electrode, two to five uniform daughter droplets can be generated simultaneously. Finally, by taking synthetic DNA targets and their corresponding molecular beacon probes as a model system, multiple potential pathogens that cause sepsis are detected rapidly on the 3D-blade-equipped DMF chip, rendering it as a promising tool for parallel diagnosis of diseases.